Implementation of agricultural technology urban farming agrivoltaic based system to increase productivity and empowerment of farmer women’s community - Moh. Hafidhuddin Karim; Markus Diantoro; N. Nasikhudin; Sri Rahayu Lestari (Journal of Community Service and Empowerment, 2023)
The need for food and the need for community empowerment, the fulfillment of new and renewable energy and productive economic activity continue to increase in line with the explosive rate of population growth, this is also what underlies the joint targets of the SDGs in points 2, 5, 7 and 8. The Cemara Hijau Farm (KWT CHF) Farmer Women's Group located in the urban area of Malang city needs solving problems in the form of land expansion, access to sustainable irrigation, and optimum irradiation of crops. In this technology implementation activity, it is carried out to increase the active role of women and increase the agricultural productivity of KWT CHF with various limitations owned. Urban Farming with the vertical concept of agrivoltaic hydroponics can maximize land use in urban areas and photovoltaic-powered LED growlight irradiation can maximize energy and reduce operational costs. Implementation is carried out with the stages of Socialization, Installation, Collaboration, Training, Monitoring and Evaluation. The results of this activity are (1) agrivoltaic technology with a capacity of 1.35 kWh, (2) planting point capacity that can be created 476 points on an area of 8 m2, (3) utilization of circulation tubs as fish farming ponds covering an area of 6 m2 with a capacity of 60 fish, and (4) a 24-hour irradiation system with LED growlight. This community service program can increase the agricultural productivity of KWT CHF, provide added value activities, and reduce agricultural operational costs so that it has a positive impact on sustainable economic value for KWT CHF. For further development, a broader follow-up implementation is needed by involving many regional points by making pilot projects at KWT CHF as pilots for other regions.